Studies of the influences of different N fertilizers and Microbion UNC bacterial fertilizer on the nutrient content of soil - Balla Kovács, Andrea; Szabó, Anita; Bartáné Szabó, Emese (Acta Agraria Debreceniensis, 2010)
A field experiment was conducted to examine the effects of different nitrogen fertilizers in combination with bacterial fertilizer on nutrient uptake of horseradish and plant available nutrients of the soil. Three different N fertilizers, ammonium-nitrate, urea and calciumnitrate (116 kg ha-1 N) in combination with Microbion UNC bacterial fertilizer (2 kg ha-1) were applied as treatments in a randomized complete block design in three replications. In this paper we presented the results of soil measurements. The soil of the experimental area was chernozem with medium sufficiency level of N and P and poor level of K. Our main results: The amount of 0.01M CaCl2 soluble inorganic nitrogen fractions, NO3 –N and NH4 +-N and also the quantity of soluble organic-N were almost the same in the soil. N fertilizers significantly increased all the soluble N fractions. The amount of NO3 –N increased to the greatest extent and the increase of organic N was the slightest. We measured the largest CaCl2 soluble NO3 - -N and total-N contents in the plots treated with ammonium-nitrate, the largest NH4 +-N in the plots treated with calcium-nitrate and the largest organic-N fraction in plots treated with urea. Bacterial inoculation also increased both soluble inorganic nitrogen forms and also total-N content of soil compared to the control. In the case of combined (artificial and bacterial fertilizer) treatments we measured lower NO3 –N, organic-N and total-N compared to the values of plots having only nitrogen fertilizer treatments. On the contrary in the plots with combined treatments the CaCl2 soluble NH4 +-N content of soil in more cases were higher than that of values with artificial fertilizer treatment. As a function of calcium-nitrate application increased AL-P2O5 and AL-K2O values were measured compared to control. Microbion UNC supplement of calcium nitrate yielded also increase in AL-P2O5 and AL-K2O values, till then supplement of ammonium-nitrate fertilizer yielded a decrease in these values compared to the control. All nitrogen fertilizers resulted in a significant decrease in AL-Mg content of soil compared to the control. Nevertheless bacterial fertilizer increased AL-Mg values in any cases.